2007
DOI: 10.1007/s00464-007-9269-x
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy in the very elderly: a review of 157 cases

Abstract: Our data suggest that colonoscopy can be safely and successfully performed in the very elderly. In patients with symptoms or suggestive radiographic findings, cancer was detected in 4.0%-60% of cases. No cases of cancer were discovered in those patients who were asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Three non-English papers were translated but only one met the inclusion criteria. We identified 62 eligible papers that provided relevant information separately for cancers and polyps [8,13-73]. Studies were published between 1960 and 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three non-English papers were translated but only one met the inclusion criteria. We identified 62 eligible papers that provided relevant information separately for cancers and polyps [8,13-73]. Studies were published between 1960 and 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Forty papers provided information about the relationship between bleeding (of any type) and colorectal cancer [13-21,23-28,30,32,33,35,37,41,42,45-47,50,51,54-56,60-66,69,72,73], and 23 of these papers [13-17,20,21,23,24,26,28,30,33,41,42,46,47,54,56,61,63,72,73] also provided information about the relationship between bleeding and polyps.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Asia have also reported higher risks of cardiovascular complications despite the fact that elderly patients on average received lower doses of sedatives [19] . Nevertheless, when taken in context, the complication rate is still quite low even for patients over 85 years of age, and in most cases colonoscopy can be done safely with appropriate monitoring and precautions [20] . Furthermore, several studies have shown that propofol sedation, despite its propensity to lower blood pressure, can be used safely in elderly patients [21][22][23] .…”
Section: Eventsmentioning
confidence: 99%
“…In this study, the very elderly had a 70% increased risk of complications compared to younger patients. Table 1 summarizes the complication rates of colonoscopy in the very elderly in studies performed during the past 10 years 16,17,18,26,27,28,29,30,31,32. The pooled complication rate of colonoscopy in the very elderly is 0-0.9%.…”
Section: Safety Of Colonoscopymentioning
confidence: 99%